Transthoracic image guided biopsy. Issue 753 (July 1988) - Dick, R.
Abstract : Transthoracic image guided biopsy is now firmly established in the armamentarium of diagnostic tests to establish the nature of a mass in the lung, pleura, mediastinum or chest wall. It may be performed under computed tomographic, ultrasonic or fluoroscopic control, and provided a fine needle technique is employed, morbidity is low. Worldwide reports show a 90% true positive yield and a false positive rate of less than 1%.